2018
DOI: 10.1038/s41550-018-0531-z
|View full text |Cite
|
Sign up to set email alerts
|

The Fermi-LAT GeV excess as a tracer of stellar mass in the Galactic bulge

Abstract: An anomalous emission component at energies of a few GeV and located towards the inner Galaxy is present in the Fermi -LAT data. It is known as the Fermi -LAT GeV excess. Using almost 8 years of data we reanalyze the characteristics of this excess with SkyFACT, a novel tool that combines image reconstruction with template fitting techniques. We find that an emission profile that traces stellar mass in the boxy and nuclear bulge provides the best description of the excess emission, providing strong circumstanti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
190
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(207 citation statements)
references
References 102 publications
13
190
0
Order By: Relevance
“…This distinctive morphology also allows the model to evade the constraints of Clark et al (2016) that ruled out a DM interpretation of the excess in terms of ultra-compact mini-halos. We note that the constraints of Clark et al (2016) do not account for more recent studies of the GC emission that revealed a more complex spatial morphology (Ackermann et al 2017;Bartels et al 2017). Finally, we expect the central massive BHs seen in nearby galactic centers, if indeed formed in the early universe, to have DM spikes, and hence to be Fermi γ-ray sources.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This distinctive morphology also allows the model to evade the constraints of Clark et al (2016) that ruled out a DM interpretation of the excess in terms of ultra-compact mini-halos. We note that the constraints of Clark et al (2016) do not account for more recent studies of the GC emission that revealed a more complex spatial morphology (Ackermann et al 2017;Bartels et al 2017). Finally, we expect the central massive BHs seen in nearby galactic centers, if indeed formed in the early universe, to have DM spikes, and hence to be Fermi γ-ray sources.…”
Section: Discussionmentioning
confidence: 93%
“…Firstly, the MWG may have a DM core (Portail et al 2017). Second, the Fermi excess can be fit, according to a reanalysis, by a stellar mass (bulge)-related profile (Bartels et al 2017).…”
Section: Global Signal and Spatial Morphologymentioning
confidence: 99%
“…Although the origin of the Galactic Center excess has not yet been singled out, recent studies have presented strong evidence that the origin of this signal is related to the stars (e.g., [28][29][30]). It is true that the Galactic center is where the most luminous annihilating DM emission is expected, however, it is difficult to disentangle a DM signal from this region due to large background and foreground uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is possible that the Galactic centre excess is not due to DM annihilation but to astrophysical sources (e.g. Bartels et al 2018), and in this case the value of the annihilation cross section determined from the Galactic centre excess should be reduced.…”
Section: Introductionmentioning
confidence: 99%